The role of Mn as dopant on the optoelectronic properties of MA(Pb1−xMnx)Cl3 single crystals. (24th May 2019) - Li, Hua-Dong; Xu, Zhi-Wen; Fu, Qiu-Ming; Zhao, Hong-Yang; Ding, Jian-Xu; Ma, Yong-Fu; Han, Yi-Bo; He, Rui; Shi, Liu; Wang, Sheng-Gao; Ma, Zhi-Bin
Abstract: Hybrid perovskite MAPbCl3 is one of the most promising candidates for the new generation optoelectronic devices. The outstanding optoelectronic performance has urged researchers to investigate more doping ions because the compositions play important roles to photoelectric properties. In this work, we demonstrate the partial replacement of Pb with Mn during the growth of MA(Pb1−x Mnx )Cl3 (x = 0, 0.01, 0.10, 0.20, 0.30) single crystals. PXPD reveals the decreased lattice parameters with the increase of Mn concentrations. AFM was carried out for analysis of surface morphology and growth mechanisms, which indicate the controlled 2D nucleation mechanism. The crystals with different Mn doping concentrations showed different optical-absorption and PL emission. The quantitative analysis of photodetector performance such as response time, photo-responsivity, external quantum efficiency and detectivity was carried out. The characterizations indicate that the MA(Pb0.9 Mn0.1 )Cl3 photodetector works best. More fundamental studies on the incorporation ions and concentrations should be carried for the searching of superior photodetectors.